Michel Serres’ Messengers - Timothy Barker (Media Theory, 2021)
Although central to his philosophy of communication, the figure of the messenger in Michel Serres’ thought has so far received little attention in English speaking media and cultural theory. This essay explores the characters of messengers that Serres develops throughout his philosophical project, focusing on the way that they allow him to develop topics such as the ethics of exchange, interdisciplinarity, pedagogy, rituals of communication and what he sees as the violence of dialectics. The discussion of Serres’ work then leads to a discussion of the messenger figure in terms of the interruptions that they can introduce to systems of exchange, ending with an exploration of what Serres’ thought may offer as we try and grapple with a new culture of miscommunication.